2006
DOI: 10.1021/jo060914p
|View full text |Cite
|
Sign up to set email alerts
|

Depsipeptide Methodology for Solid-Phase Peptide Synthesis:  Circumventing Side Reactions and Development of an Automated Technique via Depsidipeptide Units,

Abstract: The depsipeptide technique is a recently developed method for peptide synthesis which is applicable to difficult sequences when the synthetic difficulty arises because of aggregation phenomena. In the present work, application of the depsipeptide method to extremely difficult sequences has been demonstrated and a serious side reaction involving diketopiperazine formation uncovered and subsequently avoided by the appropriate use of the Bsmoc protecting group. Many other aspects of the technique have been invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
99
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 28 publications
2
99
0
1
Order By: Relevance
“…Peptides with sequences that give rise to beta sheet secondary structures, and those with very hydrophobic regions are most prone to aggregation and are generally the most problematic to synthesize [23,[28][29][30][31][32]. Sequence analysis of UBI29-41, using the Garnier-Robson and Chou-Fasman algorithms, predicted an alpha helical secondary structure for this peptide rather than a beta sheet structure [6,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Peptides with sequences that give rise to beta sheet secondary structures, and those with very hydrophobic regions are most prone to aggregation and are generally the most problematic to synthesize [23,[28][29][30][31][32]. Sequence analysis of UBI29-41, using the Garnier-Robson and Chou-Fasman algorithms, predicted an alpha helical secondary structure for this peptide rather than a beta sheet structure [6,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…140 This avoids performing O-acylation on resin, which is cumbersome and racemization prone. Two useful routes were proposed to synthesize a depsidipeptide, Boc-Thr(Fmoc-Ala)-OH (Scheme 58), which was employed for an automated synthesis of the 31-mer Cterminal segment of a globular protein, crambin.…”
Section: O-acyl Isopeptide Methods (Click or Switch Peptides)mentioning
confidence: 99%
“…Out of the entire length of the peptide, the amide bond between Gly 25 and Ser 26 was isomerized into an ester bond and the rest of the sequence was assembled following standard protocols. After cleavage from the resin followed by deprotection of the Boc group from Ser 26 , the resulting click peptide O-acyl isoAb1e42 was easily purified through HPLC owing to its solubility in aqueous media (15 mg/ml 140 Stepwise procedures, purification techniques and methods to tackle the synthetic difficulties have been described, which adopt direct application of O/N acyl migration or pseudoproline-forming reactions for the efficient synthesis of peptides that otherwise induce unfavourable conformational constraints during chain assembly.…”
Section: O-acyl Isopeptide Methods (Click or Switch Peptides)mentioning
confidence: 99%
“…Previously, we [5][6][7][8] and others [9][10][11][12] have shown that various steps along the amyloid formation pathway, including peptide/ protein misfolding, self-assembly, and amyloid formation and disassembly, can be triggered in a highly controllable manner through the incorporation of molecular switches into the amyloid-forming polypeptides, based on in situ intramolecular O! N acyl migration.…”
Section: Introductionmentioning
confidence: 99%
“…N acyl migration. [5][6][7][8][9][10][11][12][13][14][15][16] However, because of the special synthetic and purification skills required to prepare the full-length Ab switch-peptides, such peptides are not suitable for use in highthroughput screening assays. Therefore, the development of reliable model systems that are readily accessible and adaptable to automated HTS is of particular interest to understanding the mechanism of amyloid formation and facilitating the discovery of aggregation inhibitors of Ab and other amyloid-forming proteins.…”
Section: Introductionmentioning
confidence: 99%